Безперервні наближені моделі перетворювачів змінної напруги в постійну з активною корекцією коефіцієнта потужності - Шидловський, А.К.; Жаркін, А.Ф.; Пазєєв, А.Г. (Технічна електродинаміка, 2011)
Developed continuous approximation models of AC/DC converters with active power factor correction for the analysis of electromagnetic processes in the source circuits of converters. Is shown, that the use of approximate models can, while ensuring sufficient precision calculating the instantaneous output voltage, significantly reduce the time required to optimize the parameters of elements of the converters. References